Fashion lab as a factor of innovation in fashion authoring design (ModaPalavra e-periódico, 2020)
The post-industrial revolutiontransformations continue toecho in our society, allowing advances in the area oftechnology, production, and consumption of products indifferent segments, especially fashion. In view of this, thisarticle proposes to understand, in an initial and conceptualway, the use of space Fashion lab by fashion designerdesigners. It is considered that the use of this laboratory canqualify the innovation process during the production of newproducts. In this work, the basic research was used with adescriptive qualitative approach and the theoreticalfoundation contemplates the concepts of innovation, fab lab,fashion lab, and authorial design. Finally, the research resultsindicate that the principles of sharing, experimentation, andprototyping corroborate to theinnovation in fashion authoringdesign in fashion labs.
Keywords: fashion lab; authorial design; innovation